Yersinia pseudotuberculosis infection in an adult Boer goat. Issue 1 (29th June 2015) - Helmer, C; Eibach, R; Kleinschmidt, S; Ganter, M
Abstract : This case report describes a Yersinia pseudotuberculosis infection in an adult, female single pet goat kept on a dairy cattle farm. The doe showed the habitus of a chronically ill animal, with poor body condition and chronic diarrhoea, when presented at the clinic. The animal displayed a grave manifestation of the disease with severe enteritis and typhlocolitis, lymphadenitis and some up to 10 cm in diameter pyogranulomatous inflammation in the liver, spleen, pancreas, omasum and the intestinal lymph nodes. All other causative agents that might explain the described signs were ruled out ( Corynebacterium pseudotuberculosis, Mycobacterium avium subspecies paratuberculosis, tuberculosis, tumorous alterations, foreign bodies, caprine arthritis encephalitis). Goats seem to be vulnerable for yersiniosis, but in contrast to this case report, in most cases, Yersinia enterocolitica, and not Y. pseudotuberculosis, can be proved as infectious cause of yersiniosis.